A flame retardant and anti-aging electronic connecting wire sheath material and preparation method thereof
By forming an organic layer containing P elements, N elements and benzene ring structures on the surface of calcium carbonate, and adding flame retardant DOPO, the problem of insufficient flame retardant and aging resistance of existing electronic connecting wire sheath materials is solved, and higher thermal stability, flame retardant and tensile strength are achieved.
Patent Information
- Application Number
- CN202411229094.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The flame retardant and aging resistance of existing electronic connecting wire sheath materials are insufficient, which is prone to fire due to high temperatures and poor mechanical properties.
By forming an organic layer containing P elements, N elements and benzene ring structures on the surface of calcium carbonate, its compatibility and tensile strength are improved, and the flame retardant DOPO is added to improve thermal stability and flame retardant properties.
The thermal stability, flame retardant properties and tensile strength of the electronic connecting wire sheath material are significantly improved, and its anti-aging and safety are enhanced.
Smart Images

Figure BDA0005025556260000021 
Figure BDA0005025556260000051 
Figure BDA0005025556260000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic connecting wire materials and relates to a flame retardant and anti-aging electronic connecting wire sheath material and a preparation method thereof. Background Art
[0002] Electronic connecting wires are one of the components that connect electrical circuits. They mainly play the role of electrical connection and signal transmission between devices and components, components and cabinets, systems and subsystems, and keep the signal distortion and energy loss between systems from changing. The quality of electronic connecting wires is related to the reliability of the overall operation of the system equipment. Electronic connecting wires need to be equipped with sheaths. At the same time, new requirements are constantly being put forward for the performance of electronic connecting wire sheaths, especially for the insulation performance, mechanical strength, flame retardancy and other aspects of electronic connecting wire sheath materials. Most of the connecting wire sheaths currently used in system equipment are made of plastic, and their mechanical properties and flame retardancy have not reached the best effect. At the same time, the internal heat is high, and fires caused by fire of insulating parts due to electrical failures occur from time to time. Therefore, it is necessary to prepare materials with strong flame retardancy and aging resistance to increase the service life of the sheath.
[0003] The structure of the electronic connecting wire mainly includes an internal conductor, an external insulating material and a sheath. The electronic connecting wire is affected by the use environment and power consumption, and the external or internal temperature of the connecting wire is often high or even hot. In the prior art, cheap polyvinyl chloride is mostly used to prepare the external insulating material, which has poor flame retardancy and heat resistance. It is prone to aging, embrittlement and even fire after long-term use, which affects the safety of the use of the electronic connecting wire. In the prior art, calcium oxide, silicon carbide and boron nitride are added in the preparation of raw materials to improve the high temperature resistance and flame retardancy of the sheath material, tetrafluoroethylene and silicone oil are added to make the sheath easy to demold, butyl rubber and polyurethane are used to improve the waterproofness and mechanical properties of the sheath material, but the compatibility is poor, and no flame retardant structure is set, which is easy to cause a fire hazard due to a short circuit of the wire, and the flame retardancy and aging resistance of the electronic wire sheath material are not significantly improved. Summary of the invention
[0004] The object of the present invention is to provide a flame retardant and anti-aging electronic connecting wire sheath material and a preparation method thereof. The present invention forms an organic layer containing P element, N element and benzene ring structure on the surface of calcium carbonate, so that the surface changes from hydrophilic to oleophilic, improves its compatibility in the system, improves its tensile strength, and significantly improves thermal stability and flame retardancy.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A flame retardant and anti-aging electronic connecting wire sheath material, comprising the following components by weight:
[0007]
[0008] As a preferred technical solution of the present invention, the lubricant is one or more of calcium stearate, zinc sorbate and zinc stearate.
[0009] As a preferred technical solution of the present invention, the plasticizer is one or more of dioctyl phthalate, diethyl phthalate and dibutyl phthalate.
[0010] As a preferred technical solution of the present invention, the antioxidant is one or more of antioxidant 1010, antioxidant 1076 and antioxidant 168.
[0011] As a preferred technical solution of the present invention, the vulcanizing agent is N,N'-m-phenylene bismaleimide.
[0012] As a preferred technical solution of the present invention, the vulcanization aid is one of the vulcanization accelerator TMTD, the vulcanization accelerator NA-22, and the vulcanization accelerator CZ.
[0013] As a preferred technical solution of the present invention, the silane coupling agent is one or more of silane coupling agents KH-550, KH-560 and KH-570.
[0014] The invention discloses a method for preparing the modified nano calcium carbonate, comprising the following steps:
[0015] 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and mixed evenly, and then cinnamaldehyde is slowly added and heated under an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform;
[0016] 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, stirring is continued, centrifugation is performed, washing is performed, drying is performed in an oven, and grinding is performed to obtain modified nano calcium carbonate.
[0017] As a preferred technical solution of the present invention, in step 1), the stirring and mixing is stirring at a speed of 600-700 r / min for 30-45 min; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 60-70°C for 5-6 h; the washing is washing 3 times with anhydrous ethanol; and the drying temperature of the oven is 80°C.
[0018] As a preferred technical solution of the present invention, in step 1), the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 13-14:40-46:1.5-1.8:2.0-2.4; the calcium carbonate powder is calcium carbonate passed through an 80-mesh sieve.
[0019] As a preferred technical solution of the present invention, in step 2), the heating and stirring is stirring at a temperature of 70-75°C; the time for adding the flame retardant is 2 hours; the continued stirring is stirring at a temperature of 70-75°C and a speed of 200-300r / min for 20-24 hours; the washing is washing 3 times with anhydrous ethanol; the oven drying condition is drying at a temperature of 100-105°C for 1.5-2 hours.
[0020] As a preferred technical solution of the present invention, in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 48-50:120-140:0.3-0.4:30-35; the initiator is azobisisobutyronitrile; the flame retardant is flame retardant DOPO; the flame retardant DOPO is 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0021] The invention discloses a method for preparing a flame-retardant and anti-aging electronic connecting wire sheath material. The preparation method comprises the following steps: mixing epoxy resin, carbon black, modified nano calcium carbonate and silane coupling agent in an internal mixer, adding chloroprene rubber, polytetrafluoroethylene, lubricant, plasticizer, antioxidant and vulcanizing agent for mixing, adding vulcanizing agent for secondary mixing, cooling to room temperature, and obtaining the electronic connecting wire sheath material.
[0022] As a preferred technical solution of the present invention, the mixing is performed at 80-85°C for 15-20 minutes; the secondary mixing is performed at 170-190°C for 20-25 minutes and then pressure vulcanized at 10 MPa for 3-5 minutes.
[0023] Beneficial effects of the present invention:
[0024] The invention forms an organic layer containing P element, N element and benzene ring structure on the surface of calcium carbonate, so that the surface changes from hydrophilic to oleophilic, improves its compatibility in the system, improves its tensile strength, and significantly improves thermal stability and flame retardancy. DETAILED DESCRIPTION
[0025] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0026] The raw materials for the preparation of the present invention can be purchased from the market. The raw material information used in the present invention is as follows: chloroprene rubber was purchased from Shenyang Elepox Chemical Co., Ltd.; polytetrafluoroethylene with an average particle size of 30 μm was purchased from DuPont of the United States; epoxy resin, AG602, with an epoxy value of 0.96 mol / 100 g, was purchased from Shanghai Huayi Resin Co., Ltd.; carbon black is carbon black N134, which was purchased from Shanghai McLean Biochemical Technology Co., Ltd.
[0027] Example 1
[0028] A flame retardant and anti-aging electronic connecting wire sheath material comprises the following components by weight:
[0029]
[0030] The lubricant is a mixture of calcium stearate and zinc sorbate in a mass ratio of 1:1; the plasticizer is dioctyl phthalate; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 3:1; the vulcanizing agent is N, N'-m-phenylene bismaleimide; the vulcanization aid is vulcanization accelerator TMTD; and the silane coupling agent is silane coupling agent KH-550.
[0031] The preparation method of the modified nano calcium carbonate comprises the following steps:
[0032] 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and stirred and mixed, and then cinnamaldehyde is slowly added and heated under an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform; wherein the stirring and mixing is stirring at a speed of 600 r / min for 30 minutes; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 60° C. for 5 hours; the washing is washing 3 times with anhydrous ethanol; the drying temperature of the oven is 80° C.; the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 13:40:1.5:2.0; the calcium carbonate powder is calcium carbonate that has passed an 80-mesh sieve;
[0033] 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, the stirring is continued, centrifuged, washed, dried in an oven, and ground to obtain modified nano calcium carbonate; wherein the heating and stirring is stirring at a temperature of 70°C; the time for adding the flame retardant is 2h; the continued stirring is stirring at a temperature of 70°C and a speed of 200r / min for 20h; the washing is washing with anhydrous ethanol for 3 times; the oven drying condition is drying at a temperature of 100°C for 1.5h; in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 48:120:0.3:30; the initiator is azobisisobutyronitrile; and the flame retardant is flame retardant DOPO.
[0034] A method for preparing a flame retardant and anti-aging electronic connecting wire sheath material comprises the following steps:
[0035] Epoxy resin, carbon black, modified nano calcium carbonate and silane coupling agent are placed in an internal mixer for mixing, chloroprene rubber, polytetrafluoroethylene, lubricant, plasticizer, antioxidant and vulcanization aid are added for mixing, vulcanizing agent is added for secondary mixing, and then cooled to room temperature to obtain an electronic connecting wire sheath material; wherein, the mixing is performed at a temperature of 80°C for 15 minutes; the secondary mixing is performed at a temperature of 170°C for 20 minutes and then pressure vulcanized at 10MPa for 3 minutes.
[0036] Example 2
[0037] A flame retardant and anti-aging electronic connecting wire sheath material comprises the following components by weight:
[0038]
[0039]
[0040] The lubricant is a mixture of calcium stearate and zinc sorbate in a mass ratio of 1:1; the plasticizer is dioctyl phthalate; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 3:1; the vulcanizing agent is N, N'-m-phenylene bismaleimide; the vulcanization aid is vulcanization accelerator TMTD; and the silane coupling agent is silane coupling agent KH-550.
[0041] The preparation method of the modified nano calcium carbonate comprises the following steps:
[0042] 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and stirred and mixed, and then cinnamaldehyde is slowly added and heated under an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform; wherein the stirring and mixing is stirring at a speed of 635r / min for 35min; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 63°C for 5.5h; the washing is washing 3 times with anhydrous ethanol; the drying temperature of the oven is 80°C; the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 13.3:42:1.6:2.1; the calcium carbonate powder is calcium carbonate passing through an 80-mesh sieve;
[0043] 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, stirring is continued, centrifugation is performed, washing is performed, and after drying in an oven, grinding is performed to obtain modified nano calcium carbonate; wherein the heating and stirring is performed at a temperature of 72°C; the time for adding the flame retardant is 2 hours; the continued stirring is performed at a temperature of 72°C and a speed of 235 r / min for 21 hours; the washing is performed 3 times with anhydrous ethanol; the oven drying condition is dried at a temperature of 102°C for 1.7 hours; in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 48.7:127:0.33:32; the initiator is azobisisobutyronitrile; and the flame retardant is flame retardant DOPO.
[0044] A method for preparing a flame retardant and anti-aging electronic connecting wire sheath material comprises the following steps:
[0045] Epoxy resin, carbon black, modified nano calcium carbonate and silane coupling agent are placed in an internal mixer for mixing, chloroprene rubber, polytetrafluoroethylene, lubricant, plasticizer, antioxidant and vulcanization aid are added for mixing, vulcanizing agent is added for secondary mixing, and then cooled to room temperature to obtain an electronic connecting wire sheath material; wherein, the mixing is performed at a temperature of 82° C. for 17 minutes; the secondary mixing is performed at a temperature of 175° C. for 22 minutes and then pressure vulcanized at 10 MPa for 3 minutes.
[0046] Example 3
[0047] A flame retardant and anti-aging electronic connecting wire sheath material comprises the following components by weight:
[0048]
[0049] The lubricant is a mixture of calcium stearate and zinc sorbate in a mass ratio of 1:1; the plasticizer is dioctyl phthalate; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 3:1; the vulcanizing agent is N, N'-m-phenylene bismaleimide; the vulcanization aid is vulcanization accelerator TMTD; and the silane coupling agent is silane coupling agent KH-550.
[0050] The preparation method of the modified nano calcium carbonate comprises the following steps:
[0051] 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and stirred and mixed, and then cinnamaldehyde is slowly added and heated under an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform; wherein the stirring and mixing is stirring at a speed of 665r / min for 40min; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 67°C for 5.5h; the washing is washing 3 times with anhydrous ethanol; the drying temperature of the oven is 80°C; the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 13.7:44:1.7:2.3; the calcium carbonate powder is calcium carbonate passing through an 80-mesh sieve;
[0052] 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, stirring is continued, centrifugation is performed, washing is performed, and after drying in an oven, grinding is performed to obtain modified nano calcium carbonate; wherein the heating and stirring is performed at a temperature of 75°C; the time for adding the flame retardant is 2 hours; the continued stirring is performed at a temperature of 73°C and a speed of 265r / min for 23 hours; the washing is performed 3 times with anhydrous ethanol; the oven drying condition is dried at a temperature of 103°C for 1.8 hours; in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 49.3:133:0.35:33; the initiator is azobisisobutyronitrile; and the flame retardant is flame retardant DOPO.
[0053] A method for preparing a flame retardant and anti-aging electronic connecting wire sheath material comprises the following steps:
[0054] Epoxy resin, carbon black, modified nano calcium carbonate and silane coupling agent are placed in an internal mixer for mixing, chloroprene rubber, polytetrafluoroethylene, lubricant, plasticizer, antioxidant and vulcanization aid are added for mixing, vulcanizing agent is added for secondary mixing, and then cooled to room temperature to obtain an electronic connecting wire sheath material; wherein, the mixing is performed at a temperature of 83° C. for 18 minutes; the secondary mixing is performed at a temperature of 183° C. for 23 minutes and then pressure vulcanized at 10 MPa for 4 minutes.
[0055] Example 4
[0056] A flame retardant and anti-aging electronic connecting wire sheath material comprises the following components by weight:
[0057]
[0058] The lubricant is a mixture of calcium stearate and zinc sorbate in a mass ratio of 1:1; the plasticizer is dioctyl phthalate; the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 3:1; the vulcanizing agent is N, N'-m-phenylene bismaleimide; the vulcanization aid is vulcanization accelerator TMTD; and the silane coupling agent is silane coupling agent KH-550.
[0059] The preparation method of the modified nano calcium carbonate comprises the following steps:
[0060] 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and stirred and mixed, and then cinnamaldehyde is slowly added and heated under an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform; wherein the stirring and mixing is stirring at a speed of 700 r / min for 45 minutes; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 70° C. for 6 hours; the washing is washing with anhydrous ethanol for 3 times; the drying temperature of the oven is 80° C.; the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 14:46:1.8:2.4; the calcium carbonate powder is calcium carbonate passing through an 80-mesh sieve;
[0061] 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, the stirring is continued, centrifuged, washed, dried in an oven, and ground to obtain modified nano calcium carbonate; wherein the heating and stirring is stirring at a temperature of 75°C; the time for adding the flame retardant is 2 hours; the continued stirring is stirring at a temperature of 75°C and a speed of 300r / min for 24 hours; the washing is washing with anhydrous ethanol for 3 times; the oven drying condition is drying at a temperature of 105°C for 2 hours; in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 50:140:0.4:35; the initiator is azobisisobutyronitrile; and the flame retardant is flame retardant DOPO.
[0062] A method for preparing a flame retardant and anti-aging electronic connecting wire sheath material comprises the following steps:
[0063] Epoxy resin, carbon black, modified nano calcium carbonate and silane coupling agent are placed in an internal mixer for mixing, chloroprene rubber, polytetrafluoroethylene, lubricant, plasticizer, antioxidant and vulcanization aid are added for mixing, vulcanizing agent is added for secondary mixing, and then cooled to room temperature to obtain an electronic connecting wire sheath material; wherein, the mixing is performed at a temperature of 85°C for 20 minutes; the secondary mixing is performed at a temperature of 190°C for 25 minutes and then pressure vulcanized at 10MPa for 5 minutes.
[0064] Comparative Example 1
[0065] Compared with Example 3, the difference in Comparative Example 1 is that aniline is used instead of p-hydroxyaniline in Comparative Example 1, and the other components, preparation steps and parameters are the same.
[0066] Comparative Example 2
[0067] Compared with Example 3, the difference in Comparative Example 2 is the preparation of modified nano-calcium carbonate, and the other components, preparation steps and parameters are the same;
[0068] The preparation method of modified nano calcium carbonate comprises the following steps:
[0069] 1) mixing calcium carbonate powder, anhydrous ethanol and cinnamaldehyde in a mass ratio of 13.7:44:2.3, and drying in an oven to obtain a calcium carbonate preform; the calcium carbonate powder is calcium carbonate that has passed through an 80-mesh sieve;
[0070] 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, stirring is continued, centrifugation is performed, washing is performed, and after drying in an oven, grinding is performed to obtain modified nano calcium carbonate; wherein the heating and stirring is performed at a temperature of 75°C; the time for adding the flame retardant is 2 hours; the continued stirring is performed at a temperature of 73°C and a speed of 265r / min for 23 hours; the washing is performed 3 times with anhydrous ethanol; the oven drying condition is dried at a temperature of 103°C for 1.8 hours; in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 49.3:133:0.35:33; the initiator is azobisisobutyronitrile; and the flame retardant is flame retardant DOPO.
[0071] Comparative Example 3
[0072] Compared with Example 3, the difference of Comparative Example 3 is that acrolein is used instead of cinnamaldehyde in Comparative Example 3, and the other components, preparation steps and parameters are the same.
[0073] Comparative Example 4
[0074] Compared with Example 3, the difference in Comparative Example 4 lies in the preparation of modified nano-calcium carbonate, and the other components, preparation steps and parameters are the same.
[0075] The preparation method of modified nano calcium carbonate comprises the following steps:
[0076] 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and stirred and mixed, and then cinnamaldehyde is slowly added and heated in an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform; wherein the stirring and mixing is stirring at a speed of 665r / min for 40min; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 67°C for 5.5h; the washing is washing 3 times with anhydrous ethanol; the drying temperature of the oven is 80°C; the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 13.7:44:1.7:2.3; and the calcium carbonate powder is calcium carbonate passed through an 80-mesh sieve.
[0077] 2) After the calcium carbonate preform and anhydrous ethanol are stirred and mixed, the flame retardant is slowly added under heating and stirring, and stirring is continued after the addition is completed. After drying in an oven, the modified nano calcium carbonate is ground; wherein the heating and stirring is stirring at a temperature of 75°C; the time for adding the flame retardant is 2h; the continued stirring is stirring at a temperature of 73°C and a speed of 265r / min for 23h; the oven drying condition is drying at a temperature of 103°C for 1.8h; in step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol and the flame retardant is 49.3:133:33; the flame retardant is flame retardant DOPO.
[0078] Comparative Example 5
[0079] Compared with Example 3, Comparative Example 5 is different in that step 2) is not performed, and the remaining components, preparation steps and parameters are the same.
[0080] Comparative Example 6
[0081] Compared with Example 3, Comparative Example 6 is different in that calcium carbonate powder is used instead of modified nano calcium carbonate, that is, the calcium carbonate powder is not modified, and the other components, preparation steps and parameters are the same.
[0082] The electronic connecting wire sheath materials prepared in Examples 1-4 and Comparative Examples 1-6 were subjected to the following tests, respectively. The test results are shown in Table 1.
[0083] Flame retardant performance: The oxygen index of the sheath material is measured according to the method of GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method";
[0084] Tensile strength: The tensile strength of the sheath material is measured according to the method in GB / T 2951.11-2008 "General test methods for insulation and sheath materials of electric and optical cables".
[0085] The results of the various embodiments and comparative examples are shown in Table 1.
[0086] Table 1: Effect tests of various embodiments and comparative examples
[0087]
[0088]
[0089] As can be seen from the test results in Table 1, compared with Comparative Examples 1-6, the tensile strength and oxygen index of the electronic connecting wire sheath material prepared in Examples 1-3 of the present invention are significantly higher than those in Comparative Examples 1-6. This is because the present invention is connected by the imine bond between p-hydroxyaniline and cinnamaldehyde on the surface of calcium carbonate, so that the organic layer containing N elements and benzene ring structure on the formation of carbon-carbon double bonds in calcium carbonate, the hydroxyl group of p-hydroxyaniline increases the binding force of the coating and interface of calcium carbonate, and at the same time, the rigid benzene ring structure has hydrophobicity, so that the surface of calcium carbonate changes from hydrophilic to lipophilic, which can significantly improve the compatibility of calcium carbonate in the system, significantly improve the tensile strength of the composite material, and react with the carbon-carbon double bond by the rigid phenanthrene ring and the more active PH bond in the chemical structure of the flame retardant DOPO, so that the P element is grafted in the organic layer of calcium carbonate, and the thermal stability, tensile strength and flame retardant properties of the composite material are significantly improved by the benzene ring structure, N elements and P elements.
[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A flame retardant and anti-aging electronic connecting wire sheath material, characterized in that: The components include the following by weight: Chloroprene rubber 70-75 parts; 10-15 parts of polytetrafluoroethylene; 8-14 parts of epoxy resin; Carbon black 10-15 parts; 16-22 parts of modified nano calcium carbonate; 2-4 parts of lubricant; 16-20 parts of plasticizer; 3-4 parts of silane coupling agent; 1-2 parts of antioxidants; 3-4 parts of vulcanizing agent; 2-3 parts of vulcanization accelerator; The preparation method of the modified nano calcium carbonate comprises the following steps: 1) After anhydrous ethanol and calcium carbonate powder are stirred and mixed, p-hydroxyaniline is added and mixed evenly, and then cinnamaldehyde is slowly added and heated under an inert atmosphere, centrifuged, washed, and dried in an oven to obtain a calcium carbonate preform; 2) After the calcium carbonate preform, anhydrous ethanol and initiator are stirred and mixed, the flame retardant is slowly added under heating and stirring, and after the addition is completed, the mixture is continuously stirred, centrifuged, washed, dried in an oven, and ground to obtain modified nano calcium carbonate; In step 1), the mass ratio of the calcium carbonate powder, anhydrous ethanol, p-hydroxyaniline and cinnamaldehyde is 13-14:40-46:1.5-1.8:2.0-2.4; the calcium carbonate powder is calcium carbonate that has passed through an 80-mesh sieve; In step 2), the mass ratio of the calcium carbonate preform, anhydrous ethanol, initiator and flame retardant is 48-50:120-140:0.3-0.4:30-35; the initiator is azobisisobutyronitrile; and the flame retardant is flame retardant DOPO.
2. The electronic connecting wire sheath material according to claim 1, characterized in that: The lubricant is one or more of calcium stearate, zinc sorbate and zinc stearate; the plasticizer is one or more of dioctyl phthalate, diethyl phthalate and dibutyl phthalate; the antioxidant is one or more of antioxidant 1010, antioxidant 1076 and antioxidant 168.
3. The electronic connecting wire sheath material according to claim 1, characterized in that: The vulcanizing agent is N, N'-m-phenylene bismaleimide; the vulcanization aid is one of vulcanization accelerator TMTD, vulcanization accelerator NA-22, and vulcanization accelerator CZ; and the silane coupling agent is one or more of silane coupling agents KH-550, KH-560, and KH-570.
4. The electronic connecting wire sheath material according to claim 1, characterized in that: In step 1), the stirring and mixing is stirring at a speed of 600-700 r / min for 30-45 minutes; the inert atmosphere is a nitrogen atmosphere; the heating is a constant temperature treatment at a temperature of 60-70°C for 5-6 hours; the washing is washing 3 times with anhydrous ethanol; and the drying temperature of the oven is 80°C.
5. The electronic connecting wire sheath material according to claim 1, characterized in that: In step 2), the heating and stirring is stirring at a temperature of 70-75°C; the time for adding the flame retardant is 2 hours; the continued stirring is stirring at a temperature of 70-75°C and a speed of 200-300 r / min for 20-24 hours; The washing is performed by washing with anhydrous ethanol for 3 times; the oven drying condition is drying at a temperature of 100-105° C. for 1.5-2 hours.
6. A method for preparing the electronic connecting wire sheath material according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: mixing epoxy resin, carbon black, modified nano calcium carbonate and silane coupling agent in an internal mixer, adding chloroprene rubber, polytetrafluoroethylene, lubricant, plasticizer, antioxidant and vulcanization aid for kneading, adding vulcanizing agent for secondary kneading, cooling to room temperature, and obtaining electronic connecting wire sheath material.
7. The preparation method according to claim 6, characterized in that: The mixing is performed at a temperature of 80-85° C. for 15-20 minutes; the secondary mixing is performed at a temperature of 170-190° C. for 20-25 minutes and then pressure vulcanized at 10 MPa for 3-5 minutes.
Citation Information
Patent Citations
Flame-retardant cable sheath material
CN103360704A
Flame-retardant rubber cable sheath material and preparation method thereof
CN116003888A
Acid-alkali-resistant high-wear-resistant chloroprene rubber material and preparation method thereof
CN116199952A